Transcriptome Analysis Reveals Key Pathways and Candidate Genes Controlling Seed Development and Size in Ricebean (Vigna umbellata) - Verma, Sachin Kumar; Mittal, Shikha; Gayacharan; Wankhede, Dhammaprakash Pandhari; Parida, Swarup Kumar; Chattopadhyay, Debasis; Prasad, Geeta; Mishra, Dwijesh Chandra; Joshi, Dinesh Chandra; Singh, Mohar; Singh, Kuldeep; Singh, Amit Kumar (Frontiers in Genetics, 2022)
Ricebean (Vigna umbellata) is a lesser known pulse with well-recognized potential. Recently, it has emerged as a legume with endowed nutritional potential because of high concentration of quality protein and other vital nutrients in its seeds. However, the genes and pathways involved in regulating seed development and size are not understood in this crop. In our study, we analyzed the transcriptome of two genotypes with contrasting grain size (IC426787: large seeded and IC552985: small seeded) at two different time points, namely, 5 and 10 days post-anthesis (DPA). The bold seeded genotype across the time points (B5_B10) revealed 6,928 differentially expressed genes (DEGs), whereas the small seeded genotype across the time point (S5_S10) contributed to 14,544 DEGs. We have also identified several candidate genes for seed development–related traits like seed size and 100-seed weight. On the basis of similarity search and domain analysis, some candidate genes (PHO1, cytokinin dehydrogenase, A-type cytokinin, and ARR response negative regulator) related to 100-seed weight and seed size showed downregulation in the small seeded genotype. The MapMan and KEGG analysis confirmed that auxin and cytokinin pathways varied in both the contrasting genotypes and can therefore be the regulators of the seed size and other seed development–related traits in ricebeans. A total of 51 genes encoding SCFTIR1/AFB, Aux/IAA, ARFs, E3 ubiquitin transferase enzyme, and 26S proteasome showing distinct expression dynamics in bold and small genotypes were also identified. We have also validated randomly selected SSR markers in eight accessions of the Vigna species (V. umbellata: 6; Vigna radiata: 1; and Vigna mungo: 1). Cross-species transferability pattern of ricebean–derived SSR markers was higher in V. radiata (73.08%) than V. mungo (50%). To the best of our knowledge, this is the first transcriptomic study conducted in this crop to understand the molecular basis of any trait. It would provide us a comprehensive understanding of the complex transcriptome dynamics during the seed development and gene regulatory mechanism of the seed size determination in ricebeans.